Efek Hari Libur Idul Fitri Terhadap Abnormal Return Saham Di Bursa Efek Indonesia - Titik Hinawati (Universitas Muhammadiyah Magelang, 2016)
This study intends to investigate on the effect of Idul Fitr Holiday on stock abnormal return of the companies accepted in Jakarta Islamic Index. Weekly data of the last 6 years, during the period of 2009-2014, was collected to this paper. The effect of Idul Fitr on Jakarta Islamic Index is examined by comparing abnormal return one week before Idul Fitr Holiday to the other weeks and one week after Idul Fitr Holiday to the other weeks. In this study, independent t-test has been used to test the research hypotheses. The findings offer that there is effect of Idul Fitr Holiday.